2005
DOI: 10.1111/j.1475-6773.2005.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Hospital Length of Stay: Do Physicians Adapt Their Length of Stay Decisions to What Is Usual in the Hospital Where They Work?

Abstract: Objective. To test the hypothesis that physicians who work in different hospitals adapt their length of stay decisions to what is usual in the hospital under consideration. Data Sources. Secondary data were used, originating from the Statewide Planning and Research Cooperative System (SPARCS). SPARCS is a major management tool for assisting hospitals, agencies, and health care organizations with decision making in relation to financial planning and monitoring of inpatient and ambulatory surgery services and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 37 publications
0
52
0
1
Order By: Relevance
“…One of the most compelling arguments maintains that practice variations are a result of differences in resource and/or environmental constraints [12,13,19,20]. Such factors are unlikely to play a significant role in explaining the variation observed here, as this study examined variation in practice within a single hospital unit, and thus, each physician was influenced by the same organizational/environmental constraints.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…One of the most compelling arguments maintains that practice variations are a result of differences in resource and/or environmental constraints [12,13,19,20]. Such factors are unlikely to play a significant role in explaining the variation observed here, as this study examined variation in practice within a single hospital unit, and thus, each physician was influenced by the same organizational/environmental constraints.…”
Section: Discussionmentioning
confidence: 61%
“…Our study differs from previous studies examining within centre variation in that such studies focused on aspects of practice that are not completely under the physician's control (e.g. length of stay) [13][14][15], whereas our study focused on the treatment recommendations by the physicians. Thus, the results from the study presented here are not directly comparable to those of previous studies.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In their study, they showed that physicians working in two hospitals with different average lengths of stay will influence the LOS of their patients according to their dominant place of work. This implies that physicians do not adapt to changing circumstances but instead bring their old work habits to their additional place of work [16]. In our hospital, in the last 5 years, 4 internal medicine departments` directors retired and they were all replaced by new directors from the existing staff.…”
Section: Discussionmentioning
confidence: 99%
“…All inpatient and outpatient data are reported back to hospitals annually at various levels of aggregation. SPARCS data have been used in several published research articles (Pasley et al 1995;Hainsworth et al 1997;Lagoe et al 2001;Noetscher et al 2001;de Jong et al 2004).…”
Section: Study Datamentioning
confidence: 99%